Comments On The Icj’s Judgment Of 30 March 2023 Concerning Certain Iranian Assets (islamic Republic Of Iran V. United States) - Labidi, Lazhar . (Universté ELOUEd-جامعة الوادي, 2023)
On 30 March 2023, The International Court of Justice [hereafter, ICJ or Court], issued significant judgment on the merits of the case concerning Certain Iranian Assets (Islamic Republic of Iran v. United States) [hereafter, Iran v. USA] , where the Court declared that it has no jurisdiction to consider Iran's claims under Articles III, IV and V of the 1955 Treaty of Amity, Economic Relations, and Consular Rights [hereafter, Treaty of Amity], to the extent that they relate to treatment accorded to Bank Markazi. But it also found that the USA has violated its obligation for illegally blocking other assets and, accordingly, it ordered the USA to compensate Iranian companies for the injurious consequences of the violations of its international obligations. This article discusses, through the separate and dissenting opinions of the Court judges and jurisprudence, the reasons for rejecting the most important part of Iran's claims in this case, and the reason for upholding other parts of Iran's claims? To answer the question, this contribution provides an analysis of legal issues raised by the Court, and their relevance in light of unilateral measures against State-owned corporations.
المجلد14 العدد3
Keywords: International Court of Justice; Certain Iranian Assets; 30 March 2023; United States; Iran